Providing minimum bandwidth guarantees to TCP traffic in ATM networks - Zhang, Xin (2008)
In this thesis, the performances of several implementations for Guaranteed Frame Rate (GFR) service are investigated. From the simulation results, the minimum bandwidth guarantees can be provided through either intelligent buffer management with tagging and FIFO scheduling or fair queuing with tagging or Weighted Fair Buffer Allocation (W-FBA). The performance of ABR service with MCR (Minimum Cell Rate) greater than zero is also investigated in this work to compare with GFR service. Simulation results show that it can provide a low loss service with minimum bandwidth guarantee.